PENGEMBANGAN MEDIA PEMBELAJARAN IPAS METERI PERUBAHAN WUJUD BENDA BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN LITERASI SAINS DI SDK WOLOWIO - Luna, Yohana Yosefa; Dinatha, Ngurah Mahendra; Rewo, Josep Marsianus; Lawe, Yosefina Uge (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study is motivated by the low level of science literacy among students, which leads to suboptimal understanding of Natural and Social Sciences (IPAS) material, particularly regarding changes in the states of matter. Additionally, in the learning process, teachers have not utilized instructional media that support the comprehension of these concepts. Therefore, the aim of this research is to develop a Project-Based Learning (PjBL) media focused on the topic of changes in the states of matter, to enhance the science literacy skills of fifth-grade students at SDK Wolowio, Beiwali Village, Bajawa District, Ngada Regency. With a total of 19 students involved, determining the sample size and sampling technique is crucial to ensure the validity and reliability of the research findings. This study employs a Research and Development (R&D) approach by implementing the ADDIE development model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. To collect relevant data, the researcher utilized several techniques, including initial observations to assess the learning conditions, interviews with related parties to gain in-depth information, and documentation. The results of this study indicate that the developed instructional media is feasible for use and has a positive impact on improving the science literacy of students at SDK Wolowio The research findings indicate that implementing the Project-Based Learning (PjBL) model on the topic of changes in the states of matter effectively enhances the science literacy skills of fifth-grade students at SDK Wolowio. This is evident from the improvement in students' science literacy scores, increasing from 55% in the pre-test to 75% in the post-test, reflecting a significant 20% gain. The feasibility of this learning media is also supported by validation results from experts, with scores as follows: media expert at 83.3%, material expert at 83.75%, and language expert at 88%, all categorized as very valid. Additionally, positive responses were received from both teachers and students, with questionnaire scores of 86.25% and 80%, respectively. Students demonstrated enthusiasm in using the props for changes in the states of matter and were able to better understand the types and characteristics of these changes